Transitional loss of consciousness as an interdisciplinary problem of diagnosis - N. N. Petrova; N. V. Semenova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The review is devoted to the classification, diagnosis and differential diagnosis of transient loss of consciousness. The pathophysiology of transient loss of consciousness is described. It is concluded that the criteria for the differential diagnosis of transient disorders of consciousness need further development and validation. The problem of paroxysmal disorders of consciousness is interdisciplinary in nature and requires the combined efforts of doctors of different specialties to develop a unified algorithm for clinical, laboratory and instrumental diagnostics, determine management tactics and correct patient routing.